PENGEMBANGAN WISATA PANTAI SEBUAI TIMUR SEBAGAI PENDUKUNG KINERJA EKONOMI KABUPATEN KOTAWARINGIN BARAT - Tyas, Dyah Wahyuning; Arrasyid, Teddy; Sari, Wulan Purnama (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
This article explains about the potential to develop as an attraction in East Sebuai Beach tourism in Kumai District, West Kotawaringin Regency, Central Kalimantan. Location quotient and quantitative SWOT are based on analytical method. The results of the LQ and DLQ analysis are tourism sector in the Kotawaringin Barat is a non-base sector, so there is still opportunity for development and preservation. The effort to develop the East Sebuai Beach uses an aggresive strategy for development as evidenced by the result on matrix analysis SWOT formula shows an Internal Factor Analysis Strategy value of 0,06 and an External Factor Analysis Strategy value of 0,41, so that it is in first Quadrant. The SWOT matrix results show that a strength – opportunity value with a high yield of 4,06, so that factor has greatest value compared to the other factors. The appropriate East Sebuai Beach development strategy is expected to be a better tourism development plan in the future.